Stakeholder governance and the CSR of banks: An analysis of an internal governance mechanism based on game theory - An, Jiaji; Di, He; Yao, Meifang (Frontiers in Psychology, 2022)
Banks have an important social responsibility to serve the real economy and to maintain financial stability, and they also need to be responsible to borrowers and others. Against the backdrop of the COVID-19 pandemic affecting the global economy and increasing financial risks, it is particularly important for banks to assume social responsibilities. This paper theoretically analyzed the outstanding applicability of stakeholder governance theory. Using a two-stage game method, the optimal pressure intensity of social responsibility stakeholders was calculated, and the dynamic performance of shareholders was deduced. We found that the establishment of the social responsibility stakeholder governance mechanism will prompt the bank to fulfill its social responsibilities; rational social responsibility stakeholders will not lead to poor bank management due to excessive behavior; and shareholders with social responsibility can self-consciously choose investment projects with lower negative externalities. The conclusions can be summarized as follows: the participation of stakeholder and the establishment of the social responsibility function of the board of directors can help promote a bank’s social responsibility performance. This paper studied the social responsibility of banks from the new perspective of stakeholder governance, expands the theoretical boundaries, and puts forward relevant suggestions to enhance the application value of this research.